Insecticidal effects of Lamiaceae species against stored products insects - Clemente, S.=700 1 Mareggiani, G.; Brouáalis, A.; Martino, V.; Ferraro, G.
Resumenes (En, Es)
4 fig; 15 ref.
Keywords: CONTROL DE PLAGAS; INSECTICIDAS DE ORIGEN VEGETAL; EXTRACTOS VEGETALES; TRIBOLIUM CASTANEUM; LABIATAE; LAMIACEAE